(untitled) (Ocean and Coastal Research, 2022)
In recent years, the identification and economic valuation of ecosystem services have been identified as an important tool to recognize and translate nature’s contribution to people’s well-being. It is understood that assessing the economic value of ecosystem services contributes to better decision-making process regarding ecosystems, since it helps evaluation of trade-offs in alternative scenarios. Sandy beaches are among the most valuable coastal ecosystems, especially in regards to cultural services; however, they are still commonly subjected to several impacts that compromise the ecosystem integrity and capacity to provide multiple services, especially in the Global South. For this reason, management policies are crucial to reduce negative impacts. Assessing ecosystem services should be seen as a strategic approach to provide empirical support to these policies. We reviewed studies assessing and valuing sandy beach services in Brazil to identify strengths and gaps that could guide future studies. Our analysis showed that, despite Brazil being one of the leading countries in the published literature on sandy beach science, the number of studies assessing and valuing ecosystem services are small. Most of those studies are published in the native language, Portuguese, limiting the possibility of discussion and experience exchange at the international level. The services related to the use of beaches for tourism and leisure are the main category evaluated, and studies seem to focus on tourist beaches, especially those providing monetary evaluation, which follows the global trend. An increase in the number of published studies in recent years suggests a growing interest in the research subject. Based on the literature review, we discuss the results and make recommendations to guide and foster studies assessing beach services in the context of the Ocean Science Decade.